Divórcio inesperado: primeiras reações à uma perda ambígua - Eyll, Virginie Madeleine Giselle van (2020)
This research aimed to contribute to the procedural understanding of psychological distress associated with a specific form of separation, the unexpected divorce, understood as one that occurs abruptly, with a unilateral decision-making process and implies a bitter sense of abandonment and helplessness given the fact that the abandoned part had not realized that this would happen. Qualitatively, we investigated the consequences over the years following the separation focusing on the early years, identifying psychological processes experienced after the abrupt breakup, and the main factors related to facilitation and/or creating difficulties in overcoming divorce. A case study was conducted with a heterosexual woman from the middle classes of the São Paulo, from high-educational level, legally divorced, who lived in a 10-year relationship and has been divorced for approximately 3 years. The results confirm that unexpected divorces are traumatic, and there are numerous detrimental factors, such as: income decrease for women, a high degree of suffering, negative impact on physical and mental health, feelings of rejection, anger and guilt. It was also possible to verify the importance of the following processes in the recovery: giving sense and meaning to the lived, finding balance, rebuilding the identity, not internalizing anger, rediscovering hope in new relationships, being validated by others, unlink and detach itself. It was concluded that unexpected divorces should be considered by psychotherapists in their specificities, considering the traumatic potential and specificities of this crisis